2021
DOI: 10.1038/s41598-021-85890-3
|View full text |Cite
|
Sign up to set email alerts
|

Malaria transmission in landscapes with varying deforestation levels and timelines in the Amazon: a longitudinal spatiotemporal study

Abstract: The relationship between deforestation and malaria is a spatiotemporal process of variation in Plasmodium incidence in human-dominated Amazonian rural environments. The present study aimed to assess the underlying mechanisms of malarial exposure risk at a fine scale in 5-km2 sites across the Brazilian Amazon, using field-collected data with a longitudinal spatiotemporally structured approach. Anopheline mosquitoes were sampled from 80 sites to investigate the Plasmodium infection rate in mosquito communities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…falciparum -infected anophelines from rural Cruzeiro do Sul [ 37 41 ]. Laporta et al [ 40 ] showed that urban and/or peri-urban malaria is mainly caused by P . vivax -infected anophelines (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…falciparum -infected anophelines from rural Cruzeiro do Sul [ 37 41 ]. Laporta et al [ 40 ] showed that urban and/or peri-urban malaria is mainly caused by P . vivax -infected anophelines (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5 C) and 1.4% (3/210) in rural settlements (Fig. 5 D, E) [ 40 ]. Plasmodium falciparum -infection rate in anophelines is 2.6% (4/153) in the rural settlement Ramal do Caraca (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the impact of environmental deleterious human activities, such as deforestation can lead to an increase or shift of selection pressures on different pathogens, particularly viruses (Kalbus et al, 2021;Laporta et al, 2021), Figure 1). Such is the case of SARS-CoV-2, whose origin remains largely unknown (Mohammed, 2021; The Lancet Infectious, 2021) although recent findings have revealed that 96.2% of its genome shares similarities with bat- related coronaviruses; thus, suggesting its probable origin from Chiroptera (Zhou et al, 2020;Bonilla-Aldana et al, 2021).…”
mentioning
confidence: 99%